Frequency Distribution of Re-Hospitalization and Related Factors in Patients Discharged in 12 Hours from Alzahra Hospital Emergency Service, Isfahan, Iran during 2015 Spring and Summer - Mehrdad Esmailian; Mohammad Talebpoor; Ali Mehrabi-Koushki (مجله دانشکده پزشکی اصفهان, 2016)
Background: Several factors are related to emergency ward overcrowding and re-hospitalization may probably play a considerable role in this problem. Thus, the aim of this study was to determine re-hospitalization frequency and related factors in patients discharged in less than 12 hours from Alzahra hospital emergency service in Isfahan, Iran.